2009
DOI: 10.1203/pdr.0b013e31819d90a1
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Reduction of Hippocampal Brain-Derived Neurotrophic Factor Activity After Fetal-Neonatal Iron Deficiency in Adult Rats

Abstract: Fetal-neonatal iron deficiency acutely alters hippocampal biochemistry, morphology, neurotransmission and electrophysiology resulting in short-term behavioral impairments. It also down-regulates brain-derived neurotrophic factor (BDNF) expression accompanied by the upregulation of nerve growth factor (NGF), epidermal growth factor (EGF), glial-derived neurotrophic factor (GDNF), and p75 neurotrophic receptor. However, the etiology of long-term hippocampal neural transmission abnormalities and learning impairme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
106
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(117 citation statements)
references
References 75 publications
9
106
0
2
Order By: Relevance
“…3,[23][24][25][26][27][28][29][30][31] Results of a preponderance of studies have demonstrated an association between IDA in infancy and later cognitive deficits. Lozoff et al 3,25 have reported detecting cognitive deficits 1 to 2 decades after the irondeficient insult during infancy.…”
Section: Id and Neurodevelopmentmentioning
confidence: 99%
See 1 more Smart Citation
“…3,[23][24][25][26][27][28][29][30][31] Results of a preponderance of studies have demonstrated an association between IDA in infancy and later cognitive deficits. Lozoff et al 3,25 have reported detecting cognitive deficits 1 to 2 decades after the irondeficient insult during infancy.…”
Section: Id and Neurodevelopmentmentioning
confidence: 99%
“…These observations would explain the behavioral findings in human infants that have been associated with ID. [29][30][31] Therefore, taking into account that iron is the world's most common single-nutrient deficiency, it is important to minimize IDA and ID among infants and toddlers, even if an unequivocal relationship between IDA and ID and neurodevelopmental outcomes has yet to be established.…”
Section: Id and Neurodevelopmentmentioning
confidence: 99%
“…Relative mRNA levels were calculated relative to an internal standard cDNA sample. Quantitative RT-PCR for brain-derived neurotropic factor isoform IV (Bdnf IV) and early growth response factor 1 (Egr1) was performed on cDNA equivalent to 20 ng of total RNA, as previously described (29).…”
Section: Brain Mrna Analysismentioning
confidence: 99%
“…Moreover, iron-deficient (ID) rat pups have decreased energy metabolism, abnormal neuronal morphology and neurotransmission, and reduced expression of genes critical for neural plasticity in the hippocampus, particularly during the period of peak hippocampal dendritogenesis, synaptogenesis, and myelination (10,16,21,34,35,48,51,60). These abnormalities in gene expression and neuronal morphology can persist beyond the period of early iron deficiency into adulthood (10,61).…”
mentioning
confidence: 99%